THE EFFECT OF PROFİTABİLİTY ON BUSİNESS SUCCESS İN BIST FOREST, PAPER, PRİNTİNG INDEX (Third Sector Social Economic Review, 2023)
This study examines multi-criteria decision-making uses such as LOPCOW and WASPAS, which aim to reduce financial costs in Turkey's BIST forest, paper and printing business. The study provides a summary of the sector's literature and demonstrates the successful application of these methods in various industries. The LOPCOW method plays an effective role in analyzing complex criteria. The financial performance of companies was evaluated using 10-year profitability ratios in the study. Return on Equity (ROE) was generally identified as the most significant indicator, reflecting companies' financial performance the best. Gross Profit Margin (BKM) generally held lower importance, while Return on Assets (ROA) and Net Profit Margin (NKM) were considered less important compared to other indicators. The WASPAS method has been utilized in various applications across different sectors. In this study, an analysis based on WASPAS scores was conducted to assess companies' profitability performance. Alkim Kâğıt was consistently identified as the most profitable firm, while Viking Kâğıt emerged as the least profitable company. The results of this study highlight the significance of ROE in evaluating companies' financial performance. Additionally, suggestions were made to further explore sectoral differences, analyze management and operational strategies, develop appropriate policies for policymakers, and enhance the knowledge of investors and company executives through additional education.
Keywords: BIST; Forest Paper Printing Index; Profitability; Business Success; LOPCOW – WASPAS